E-nstructions: Using electronic instructions in laboratory experiments - Katrin Schmelz (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
E-nstructions facilitates the use of electronic instructions in computerized laboratory experiments. This tool has been primarily designed to be used in combination with z-Tree (Fischbacher, 2007), but it should work in combination with other experimental softwares which help developing and conducting experiments. This article provides a set of guidelines for the installation and the use of E-nstructions.
Keywords: C91; C92; 330; Experiments; Experimental software; instructions; Experimentelle Ökonomik; Computergestütztes Verfahren; PC-Software